2016
DOI: 10.1515/jpm-2015-0321
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of small for gestational age preterm singletons: a population-based cohort study

Abstract: Being SGA further complicates preterm births after 30 weeks of gestation but not earlier. This might suggest that an extended period in the hostile intrauterine environment, or that being born at <30 weeks, is bad enough and is not further aggravated by being SGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…We identified a 3.1-fold higher risk of BPD among SGA preterm infants compared with non-SGA preterm infants, which was in accordance with previous studies that have reported a 2-6-fold higher risk of BPD for SGA preterm infants (3,22,23). A large proportion of SGA preterm…”
Section: Discussionsupporting
confidence: 91%
“…We identified a 3.1-fold higher risk of BPD among SGA preterm infants compared with non-SGA preterm infants, which was in accordance with previous studies that have reported a 2-6-fold higher risk of BPD for SGA preterm infants (3,22,23). A large proportion of SGA preterm…”
Section: Discussionsupporting
confidence: 91%
“…Infants born to preeclamptic mothers had significantly greater birth weights and GAs, and the female predominance and SGA proportion were greater in this group than in the control group. SGA status is a common complication of preeclampsia, with a widely ranging incidence of 13.36–52% 11,14,3840 . In this study, the incidence of SGA in the preeclamptic group was very high, perhaps due to the application of inclusion criteria according to birth weight instead of GA, and thus the enrollment of more SGA infants.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors influence the outcomes of RDS in infants. Previous studies have reported that gestational age, [ 5 ] use of auxiliary ventilation, [ 6 ] selective cesarean section, severe birth asphyxia, maternal fetal infection, and male sex are closely correlated with full-term neonatal RDS outcomes. [ 7 ] Compared with females of the same gestational age, male preterm infants are at greater risk of developing RDS, and need more initial respiratory and circulatory support.…”
Section: Introductionmentioning
confidence: 99%